Towards more walkable streets. An assessment method applied to school areas in Parma - Rossetti, Silvia; Caselli, Barbara; Torrisi, Vincenza (TeMA - Journal of Land Use, Mobility and Environment, 2024)
It is well known that urban areas near schools are often characterised by excessive motorised traffic, making access to school facilities difficult and dangerous on foot, especially for children. Increasing walkability of these areas can indeed lead to multiple benefits: safer streets, cleaner air, a more pleasant public space that encourages social uses and the adoption of healthier lifestyles. For these reasons, scientific literature has recently focused on school streets/squares, and their possible regeneration, also through tactical urbanism. Even Italian legislation have recently introduced the concept of “school zones”. Methods and tools are, therefore, needed to delimitate these zones and assess their walkability and quality to select appropriate interventions. Within this framework, the paper applies a GIS-based methodology to calculate a School Walkability Index (SWI), providing a score for catchment areas around schools. The method is applied in the 3-, 10- and 15-minute pedestrian isochrones around primary schools in Parma. Data to perform the walkability assessment have been collected through in-field inspections. This evaluation enables the identification of low walkability levels and punctual criticalities. The outcomes of the research can be helpful to public administrations engaged in improving school accessibility and the social vocation of the surrounding public spaces.